The Kurdish political and artistic making by the transborder perception in the interstitial spaces - Sustam, Engin (UXUC - User Experience and Urban Creativity, 2021)
This article focuses on the recontextualization of the interstitial space over the last decade in Kurdish space. It will specifically focus on the Middle East territories between Turkey and Syria. The aim of this article is to investigate how the urban interstices have affected the political mobilization of the stateless Kurdish society and state control process in the conflicted public sphere. The previously mentioned interstitial urban space is important for Kurdish mobility. The ‘Kurdish space, first of all, bears a case of intra-state question in the Middle East (Turkey, Iran, Iraq and Syria). The term ‘interstitial space or urban interstices’ (‘openness in the city’, Nicolas-Le Strat, 2004) encompasses a multitude of concepts that are multifaceted (from conceptualisation to institutionalizing). The urban interstice in the Kurdish space signifies the invisibility of the minority’s space in the becoming and a space, which gives the possibility of also creating Kurdishness in the place of the conflict. As pointed out by Sanò, Storato, and Puppa in their article(2021, p.3): ‘The (in)visibility and the emptiness that characterise these interstitial spaces make them a source of autonomy.’ At the same time, Kurdish space is positioned in relation to its new subjectivity constituting emancipatory space and decolonial corpus around this stateless society practice by deploying the urban interstitial spaces in big cities like Diyarbakir in Turkey and Qamichli of Rojava in Syria.